Lack of specificity in the effect of interval training on endurance cycling performance - Stepto, N. K.; Hopkins, W.; Hawley, J. A.; Dennis, S. (Medicine & Science in Sports & Exercise, 1998)
The best intensity and duration for improving the 40-km cycling performance were studied. The tests with 20 provincial-level cyclists led to the following conclusions: The most effective interval training for 40-km cycling performance appears to be 4-min workouts around race pace. Very short, very intense workbouts (30 second at twice the pace) may also enhance peformance.